Studies in law, politics, and society. Vol. 35 - Sarat, Austin (Emerald, 2005)
This volume of "Studies in Law, Politics, and Society" presents a diverse array of articles by an interdisciplinary group of scholars. Their work spans the social sciences, humanities, and the law. Those scholars examine the nature of family and the intersection of family and law, the way contexts shape legal actors, and the nature of rights and resistance. The articles published here exemplify the exciting and innovative work now being done in interdisciplinary legal scholarship.
Keywords: Law -- General.; Political Science -- History & Theory.; Jurisprudence & general issues.; Politics & government.; Sociological jurisprudence.; Political sociology.; Law -- Political aspects.; elektronické knihy; electronic books